2020
DOI: 10.3389/fpsyg.2020.01898
|View full text |Cite
|
Sign up to set email alerts
|

How and When Does Inclusive Leadership Curb Psychological Distress During a Crisis? Evidence From the COVID-19 Outbreak

Abstract: Traumatic events such as a pandemic shatter the assumption of the workplace as a safe place. Nurses face risks of life-threatening infection, which can create psychological distress. Quality of care for infected patients depends on mental well-being of nurses which calls for research on predictors of stress among health care workers. Responding to a call for research on the effects of leadership styles on psychological distress during traumatic events, this paper uses the theoretical lens of social exchange th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
81
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 96 publications
(144 reference statements)
3
81
0
3
Order By: Relevance
“…Notably, the 57 studies that found that female sex was a significant risk factor spanned six different infectious diseases (MERS, SARS, COVID-19, H1N1, H7N9, and SARS), suggesting that being a female HCW increases vulnerability for distress more generally when working during an infectious outbreak. Notably, among the studies 30 studies that did not find that being female created significant risk for distress, eleven (36.6%) were conducted with nurses and included predominantly female participants ( 24 , 43 , 44 , 59 , 70 , 79 , 80 , 89 , 108 , 140 , 153 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the 57 studies that found that female sex was a significant risk factor spanned six different infectious diseases (MERS, SARS, COVID-19, H1N1, H7N9, and SARS), suggesting that being a female HCW increases vulnerability for distress more generally when working during an infectious outbreak. Notably, among the studies 30 studies that did not find that being female created significant risk for distress, eleven (36.6%) were conducted with nurses and included predominantly female participants ( 24 , 43 , 44 , 59 , 70 , 79 , 80 , 89 , 108 , 140 , 153 ).…”
Section: Resultsmentioning
confidence: 99%
“…In nurses working during the SARS outbreak in Canada, higher perceived organizational support in the form of receiving positive performance feedback from doctors and co-workers, was associated with lower perceptions of SARS-related threat and reduced feelings of emotional exhaustion ( 59 ). Similarly, nurses, physicians, and HCW working during the MERS, COVID-19, and SARS outbreaks who perceived support from their supervisors and colleagues, experienced better mental health in the form of lower PTSD symptoms, lower distress, and being less likely to develop psychiatric symptoms, respectively ( 24 , 28 , 41 , 54 , 59 , 70 , 79 , 80 , 88 , 99 , 116 ).…”
Section: Resultsmentioning
confidence: 99%
“…With regard to work engagement, from an international perspective, studies such as the one by Ahmed et al [ 36 ] on a sample of 497 registered nurses from five hospitals in Wuhan offered even higher values in levels of work engagement during the health crisis. In fact, they obtained high values in vigor 5.39 (SD = 0.46), dedication 5.51 (SD = 0.41), and total work engagement 5.44 (SD = 0.41), and very high values in absorption 5.43 (SD = 0.45).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that improving the level of work engagement of nurses increases job satisfaction and the sense of coherence, and therefore also their emotional well-being in the development of their profession [ 15 , 36 ]. This improvement in emotional well-being, closely related to increased work engagement, promotes increased resilience to the stress and work overload that characterizes healthcare needs in the current COVID-19 pandemic [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…What is the role of the leader in making the most of the human capital in their organizations during times of crises? (see Ahmed, Zhao, & Faraz, 2020 for example). How can employee knowledge, skills, and abilities be developed and harnessed in these contexts? I am hoping that we all experience many positive surprises this upcoming year.…”
Section: Concluding Commentsmentioning
confidence: 99%